Robust watermarking using hand gesture for enhanced authentication - Seng, W.C.; Fong, L.L.; Shing, N.L.; Noudeh, S.A.H. (2011)
According to Bell Labâs finding, a large percentage of passwords chosen by users were easy to decode in a short period of time. As users realize the importance of security and privacy, there is a rapid increment of higher security demand in authentication systems. In this work, a gesture authentication system built with a robust watermark algorithm is presented. This biometric authentication system is divided into two modules, which are watermark embedding module and watermark detection module. For watermark embedding module, the first level of DWT is applied to the host image. Hand gesture image (watermark) is embedded into a host image using LSB and the redundant embedding method. For watermark detection module, the watermarked image will be processed and the majority voting method is used to retrieve the watermark from watermarked image. Non-blind watermarking is emphasized in watermark detection module. Various tests have been evaluated in both modules. Firstly, the effectiveness and fidelity tests are evaluated for watermark embedding module and both results are pass. Secondly, all the detection effectiveness test (pass) and robustness test using JPEG Compression (98.34), Gaussian Noise (98.34), Median Filtering (85.48) and Contrast Adjustment (98.34) have satisfying results. As conclusion, this algorithm is suitable to be applied in any type of image authentication system.